2020
DOI: 10.1016/j.kint.2020.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in patients hospitalized with COVID-19

Abstract: The rate of acute kidney injury (AKI) associated with patients hospitalized with Covid-19, and associated outcomes are not well understood. This study describes the presentation, risk factors and outcomes of AKI in patients hospitalized with Covid-19. We reviewed the health records for all patients hospitalized with Covid-19 between March 1, and April 5, 2020, at 13 academic and community hospitals in metropolitan New York. Patients younger than 18 years of age, with end stage kidney disease or with a kidney t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

165
1,527
36
119

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 1,280 publications
(1,847 citation statements)
references
References 28 publications
165
1,527
36
119
Order By: Relevance
“…The same group in another publication observed proteinuria in 65.8% of 333 hospitalized patients [14]. Hirsch et al [15] found a prevalence of 42.1%, by dipstick results, in 646 patients in New-York City.…”
Section: Discussionmentioning
confidence: 83%
“…The same group in another publication observed proteinuria in 65.8% of 333 hospitalized patients [14]. Hirsch et al [15] found a prevalence of 42.1%, by dipstick results, in 646 patients in New-York City.…”
Section: Discussionmentioning
confidence: 83%
“…Thirdly, mechanical respiratory support including the level of PEEP is critical in developing AKI in SARS-COV-2. As described by Hirsch et al, SARS-CoV-2 ventilated patients are at greater risk of developing AKI than non-ventilated ones (89.7% vs. 21.7%), especially during the rst 24 hours following intubation (31).…”
Section: Discussionmentioning
confidence: 95%
“…Overall, COVID-19 patients were included in our meta-analysis. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] The pooled estimated incidence of AKI in all hospitalized COVID-19 patients was 12.0% (95% CI: 9.0%-15.0%, Fig. 2), and a signi cant heterogeneity (I 2 = 98%, Chi-square = 0.19, P < 0.01) was observed ( Table 3).…”
Section: Literature Search and Study Characteristicsmentioning
confidence: 99%